2017
DOI: 10.1007/s11356-017-8505-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of straw and biochar amendments on aggregate stability, soil organic carbon, and enzyme activities in the Loess Plateau, China

Abstract: Soil from the Loess Plateau of China is typically low in organic carbon and generally has poor aggregate stability. Application of organic amendments to these soils could help to increase and sustain soil organic matter levels and thus to enhance soil aggregate stability. A field experiment was carried out to evaluate the effect of the application of wheat straw and wheat straw-derived biochar (pyrolyzed at 350-550 °C) amendments on soil aggregate stability, soil organic carbon (SOC), and enzyme activities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
75
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(94 citation statements)
references
References 80 publications
11
75
2
Order By: Relevance
“…The EEG content exhibited a behavior similar to the carbon content in micro and macro-aggregates of the soil (Figure 3E and F), which reinforces the concept that EEG is an important source of soil organic carbon (Zhang et al, 2017). The highest EEG levels were found in the AC system, differing between the depths evaluated only in the EEG-MAC (p < 0.05), and the systems with the least EEG were the MA and PA ( Figure 3E).…”
Section: Easily Extractable Glomalin-related To Soil Protein In Microsupporting
confidence: 82%
See 1 more Smart Citation
“…The EEG content exhibited a behavior similar to the carbon content in micro and macro-aggregates of the soil (Figure 3E and F), which reinforces the concept that EEG is an important source of soil organic carbon (Zhang et al, 2017). The highest EEG levels were found in the AC system, differing between the depths evaluated only in the EEG-MAC (p < 0.05), and the systems with the least EEG were the MA and PA ( Figure 3E).…”
Section: Easily Extractable Glomalin-related To Soil Protein In Microsupporting
confidence: 82%
“…A higher ASI was expected in the sys- tem with greater species diversity (AC), including the reference area (CR), since both could promote a greater diversity of root exudates of different compositions, guaranteeing greater carbon source diversity in the soil system (Silva et al, 2016a). In addition to the biological diversity of natural systems that improves the stability of soil aggregates, another controversial aspect refers to spontaneous burning in the Cerrado that may or may not promote an increase in the stability of these aggregates (Thomaz, 2017;Hobley et al, 2017;Zhang et al, 2017). Despite this, the ASI value found for the management systems lies within the range commonly found for tropical soils (82 ± 6 %) (Thomaz, 2017).…”
Section: Aggregate Stability Index (Asi)mentioning
confidence: 99%
“…1a, the fraction of <0.05 mm was the dominant aggregate size, accounting for ∼70% of the total weight. Study of Zhang et al (2017) demonstrated that the greatest proportion of soil aggregates were in smaller size classes. Incorporation of straw and biochar decreased the proportion of >0.25‐mm size fractions (>1‐mm and 0.25‐ to 1‐mm fractions) but increased the amount of <0.25‐mm size fractions (0.05‐ to 0.25‐mm and <0.05‐mm fractions) in this soil.…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed that SOC can be stabilized by both the soil silt-clay fractions (<0.053 mm) and microaggregates (0.053-0.25 mm), which significantly influence the accumulation and bioavailability of SOC (Six and Paustian, 2014). Although a positive effect of both straw and derived biochar on SOC content and soil aggregation has been reported (Zhang et al, 2017), debate continues on the influence of biochar amendment on soil aggregate distributions and associated SOC contents (Pituello et al, 2018). Studies found an increase in SOC content among different aggregate fractions after biochar amendment, whereas others obtained a decreasing tendency (Pituello et al, 2018).…”
Section: Three-year Field Observation Of Biochar-mediated Changes In mentioning
confidence: 99%
See 1 more Smart Citation